Straightforward and robust synthesis of monodisperse surface-functionalized gold nanoclusters - Silvia Varela-Aramburu; Richard Wirth; Chian-Hui Lai; Guillermo Orts-Gil; Peter H. Seeberger (Beilstein Journal of Nanotechnology, 2016)
Gold nanoclusters are small (1–3 nm) nanoparticles with a high surface area that are useful for biomedical studies and drug delivery. The synthesis of small, surface-functionalized gold nanoclusters is greatly dependent on the reaction conditions. Here, we describe a straightforward, efficient and robust room temperature one-pot synthesis of 2 nm gold nanoclusters using thioglucose as a reducing and stabilizing agent, which was discovered by serendipity. The resultant monodisperse gold nanoclusters are more stable than those generated using some other common methods. The carboxylic acid contained in the stabilizing agent on the cluster surface serves as anchor for nanocluster functionalization. Alternatively, the addition of thiols serves to functionalize the nanoclusters. The resulting non-cytotoxic nanoclusters are taken up by cells and constitute a tuneable platform for biomedical applications including drug delivery.